Synthesis of Poly [(N – Acryl) Substituted Hydrazone] from Condensation of Poly Acryloyl Chloride with Various Schiff Bases - Al – Rekabi, Zena G (Al-Nahrain Journal of Science, 2011)
In the present investigation, new eight polymers of poly [(N–acryl) substituted hydrazone ] were synthesized by two steps; first step includes treatment of 2, 4dinitro phenyl hydrazine with different aldehydes or Ketones to obtain Schiff bases. The second step includes Condensation hydrazone groups (Schiff bases) with poly acryloyl chloride in DMF to obtain poly [(N – acryl) substituted hydrazone ]. All the synthesized polymers were characterized by FT– IR spectrum, UV spectrum, melting and softening points and solubility, then study the Biological activity for some of these new polymers.